Analytical methods for food safety by mass spectrometry. - Pang, Guo-Fang (Academic Press, an imprint of Elsevier : Chemical Industry Press, 2018)
Analytical Methods for Food Safety by Mass Spectrometry, Volume Two: Veterinary Drugs systematically introduces the Pesticide and Veterinary Drug Multiresidues Analytical Methods, with discussions on 69 veterinary drug multiresidues chromatic-MS analytical methods that are capable of detecting over 200 veterinary drugs and chemical residues of 20 categories, such as iA-agonists, iA-lactams, aminoglycosides, amphenicols, anabolic hormone, anabolic steroids, avermectins, benzimidazole, cephalosporins, glucocorticoid steroids, macrolides, nitrofurans, nitroimidazoles, NSAIDs, polyether, polypeptides, progestagens, pyrazolones, quinolones, quinoxalines, sedatives, sulfonamides, synthetic estrogens, tetracyclines, thyreostats, and other toxins in animal and poultry tissues, acquatic products, milk, milk powders and bee products. This valuable book can be used as reference for not only university students, but also technical personnel of different specialties who are engaged with study and applications, such as food safety, agricultural environment protection, pesticide development, and utilization in scientific research units, institutions and quality inspection organizations.